On the Transformation of Thinking on Personal Responsibility Towards Requirements of Environmental Ethics in Slovakia - Vadíková, Katarína Mária (Studia Ecologiae et Bioethicae, 2022)
The main purpose of this paper is to confirm a remarkable transformation in contemporary thinking on responsibility for the environment in Slovakia, since the Velvet Revolution (1989). Terminology is derived from Guardini’s educational, environmental ethics of responsibility, and actualised via Bauman-Lipovetsky’s critics of the post-modern way of thinking. Comparisons of the situation in thinking on responsibility for the environment, before and after the Velvet revolution, are based on an analysis of findings of various inter-disciplinary research-projects, argued via enviro-criminal cases mentioned in the Slovak media, existentially verified by the author herself, as a living witness, and fostered by appropriate Slovak legislation. The main findings of the paper are as follows: liquidity of thinking on responsibility for the environment was confirmed; transformation of the Slovak mentality is remarkable – there are still enough people, who transfer responsibility, to be taken by “competent ones” (Homo Sovieticus mentality); however, many influencers and volunteers, also politicians, are pro-environment engaged in various public projects (‘The Man of the Velvet Revolution mentality’); people are more aware of their environmental rights and duties, and feel more invited to take personal responsibility for the environment. Conclusion: Slovaks are interested in pro-environmental projects, if it pays off, and if they do not feel alone in pro-environmental efforts.